Komunikasi Pemasaran Digital Pokdarwis Dalam Meningkatkan Jumlah Pengunjung di Bukit Sosogan Kabupaten Karanganyar - Puspitasari, Putri Mia; Riyanto, Buddy; Widiyowati, Estu (Solidaritas, 2024)
This research aims determine the digital marketing communications of Pokdarwis in increasing the number of visitor on Bukit Sosogan Kabupaten Karanganyar. The data collection and research process for this thesis was carried out from may to june 2024 with three sources. The thesis data collection technique was carried out using observation and qualitative interviews with sources related to Bukit Sosogan digital marketing communications. The result of research and interviews show that management has maximized Bukit Sosogan marketing communications using social media Instagram and Youtube, but the Bukit Sosogan maangement has not maximized interaction with followers on the Youtube social media platform.